Outcomes in arthroscopic surgery and proposal rehabilitative treatment in femoral acetabular impingement syndrome - Di Benedetto, Paolo; Vidi, Daniele; Buttironi, Michele Mario; Mancuso, Francesco; Ricciarelli, Marco; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2022)
Background and aim of the work Femural Acetabular impingement syndrome (FAIS) is a patologic condition that can lead to hip pain, functional limitation and stiffness. In the last few decades orthopedics and physiotherapists have improved both surgery and riabilitative treatment leading to a better and better treatment. The target of this paper il to verify the efficiency of an early and multimodal physiotherapic treatment after and arthroscopic surgery of the FAIS Materials and Methods We performed arthroscopic treatment and rehabilitation on 19 patients with mean age of 37±8,3 years, 12 males and 7 females. Each patient has been evaluated preoperatively (T0), postoperatively after 6 week (T1) and after 3 months of follow up (T2), the assessment was carried out by: administration of the VAS and WOMAC score for pain and function and joint examination of active hip movement through an inertial sensor system. Results VAS score shows a decrease of pain after 6 week (mean decrease was 36%) and after 3 months (mean decrease was 33%). WOMAC score shows an increase of the funcional performance of the hip after 3 weeks and after 3 months (in both phases the mean score increase of the 44%) At last, the analysis of the active movement and of the hip joint showed a generalized increase in all movements both 6 weeks and 3 months after surgery, in particular for flexion (with the knee flexed) and internal rotation movements. of the hip. Conclusion The results of this study are in line with the current scientific literature and the protocol used represents a valid tool to complete the surgical treatment. The proposal of an early, intensive treatment combined with hydrokinesitherapy seems to be safe and effective, however further studies are needed (increasing the sample size) to investigate the results.